Regulatory T cell frequencies are increased in preterm infants with clinical early-onset sepsis. (12th June 2016) - Pagel, J; Hartz, A; Figge, J; Gille, C; Eschweiler, S; Petersen, K; Schreiter, L; Hammer, J; Karsten, C M; Friedrich, D; Herting, E; Göpel, W; et al.
Summary: The predisposition of preterm neonates to invasive infection is, as yet, incompletely understood. Regulatory T cells (Tregs ) are potential candidates for the ontogenetic control of immune activation and tissue damage in preterm infants. It was the aim of our study to characterize lymphocyte subsets and in particular CD4 + CD25 + forkhead box protein 3 (FoxP3) + Tregs in peripheral blood of well-phenotyped preterm infants ( n  = 117; 23 + 0 – 36 + 6 weeks of gestational age) in the first 3 days of life in comparison to term infants and adults. We demonstrated a negative correlation of Treg frequencies and gestational age. Tregs were increased in blood samples of preterm infants compared to term infants and adults. Notably, we found an increased Treg frequency in preterm infants with clinical early-onset sepsis while cause of preterm delivery, e.g. chorioamnionitis, did not affect Treg frequencies. Our data suggest that Tregs apparently play an important role in maintaining maternal-fetal tolerance, which turns into an increased sepsis risk after preterm delivery. Functional analyses are needed in order to elucidate whether Tregs have potential as future target for diagnostics and therapeutics.